CLOSE PYOMETRA WITH BILATERAL FOLLICULAR CYST IN A BITCH - KUMAR, A; KUMAR, U; DAS, S (The Indian Journal of Animal Reproduction, 2016)
Five year old bitch having high temperature, pale mucous membranes, moderate dehydrate , distended abdomen, anorexia and vomition with marked leucocytosis, neutrophila, monocytosis, low heamoglobin, elevated blood urea nitrogen and distended uterus was confirmed as a case of close pyometra with bilateral follicular cyst in a bitch.